2021
DOI: 10.3390/ijms222111895
|View full text |Cite
|
Sign up to set email alerts
|

Bean and Pea Plastoglobules Change in Response to Chilling Stress

Abstract: Plastoglobules (PGs) might be characterised as microdomains of the thylakoid membrane that serve as a platform to recruit proteins and metabolites in their spatial proximity in order to facilitate metabolic channelling or signal transduction. This study provides new insight into changes in PGs isolated from two plant species with different responses to chilling stress, namely chilling-tolerant pea (Pisum sativum) and chilling-sensitive bean (Phaseolus coccineus). Using multiple analytical methods, such as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…This confirms that the pre-treatment of JA plays an important role in preventing chloroplast degradation by enhancing the production of protective antioxidant compounds (e.g., α-tocopherols) which tend to conserve membrane against ROS (Bashandy et al, 2020 ; Younes et al, 2020 ) and hinder photoinactivation of PSII (Havaux et al, 2005 ). In this regard, plastoglobules are a sink of lipophilic antioxidants such as α-tocopherol where main enzymes have been present in their membranes (Wójtowicz et al, 2021 ). The data of current work found that α-tocopherol content elevated parallel to a higher number of plastoglobules as was reported by Wójtowicz et al ( 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms that the pre-treatment of JA plays an important role in preventing chloroplast degradation by enhancing the production of protective antioxidant compounds (e.g., α-tocopherols) which tend to conserve membrane against ROS (Bashandy et al, 2020 ; Younes et al, 2020 ) and hinder photoinactivation of PSII (Havaux et al, 2005 ). In this regard, plastoglobules are a sink of lipophilic antioxidants such as α-tocopherol where main enzymes have been present in their membranes (Wójtowicz et al, 2021 ). The data of current work found that α-tocopherol content elevated parallel to a higher number of plastoglobules as was reported by Wójtowicz et al ( 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, plastoglobules are a sink of lipophilic antioxidants such as α-tocopherol where main enzymes have been present in their membranes (Wójtowicz et al, 2021 ). The data of current work found that α-tocopherol content elevated parallel to a higher number of plastoglobules as was reported by Wójtowicz et al ( 2021 ). Thus, JA instigates cellular signaling under salinity stress through mediating α-tocopherol content.…”
Section: Discussionmentioning
confidence: 99%
“…AFM measurements were performed with an Agilent 5500 microscope (Agilent, Santa Clara, CA, USA), working in contact and tapping mode, under the control of PicoView software as previously described 53 . OMVs were immobilized on freshly cleaved mica, with poly-L-lysine as a stabilizing matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Other parameters were used as pre-set in the software. Unique and razor peptides were used for quantification enabling protein grouping (razor peptides are the peptides uniquely assigned to protein groups and not to individual proteins) 53 55 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, PCA can be combined with regression coefficients obtained from various spectral curves, such as OJIP, which represent the fluorescence kinetics over the first few seconds of illumination, and hyperspectral reflectance, transmittance, and absorbance curves. This combination allows for more comprehensive analysis by combining biochemical and biophysical insights [31]. Such a multifaceted approach enhances the understanding of plant responses and interactions with their environment, aiding in more accurate and predictive modelling of plant physiology and agronomy by remote-sensing techniques [4][5][6]32].…”
Section: Introductionmentioning
confidence: 99%